2017
DOI: 10.1159/000475475
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Anal Function by Adipose-Derived Stem Cell Sheets

Abstract: Aim: One of the most troublesome complications of anal preserving surgery is anal sphincter dysfunction. The aim of this study was to evaluate functional recovery after implantation of adipose-derived stem cell (ADSC) sheets, novel biotechnology, for an anal sphincter resection animal model. Methods: Eighteen female Sprague-Dawley rats underwent removal of the nearest half of the internal and external anal sphincter muscle. Nine rats received transplantation with ADSC sheets to the resected area while the rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 19 publications
0
33
1
Order By: Relevance
“…This study rst developed an IAS-speci c incontinence animal model with molecular and histologic changes in SMCs in the IAS. Our incontinence model deliberately targeted SMCs in the IAS and can reduce the bias caused by involving skeletal muscle cells in previous animal models in which anal sphincterotomy was performed at both the IAS and EAS [20][21][22][23]. In the established model, implanted hADScs induced augmentation of SMCs at the injured site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study rst developed an IAS-speci c incontinence animal model with molecular and histologic changes in SMCs in the IAS. Our incontinence model deliberately targeted SMCs in the IAS and can reduce the bias caused by involving skeletal muscle cells in previous animal models in which anal sphincterotomy was performed at both the IAS and EAS [20][21][22][23]. In the established model, implanted hADScs induced augmentation of SMCs at the injured site.…”
Section: Discussionmentioning
confidence: 99%
“…However, to investigate the functional recovery of resting pressure or SMCs in the IAS, a few animal models representing the pathophysiology of a dysfunctional IAS have been reported [20][21][22]. After applying intramuscular or intravascular injection of mesenchymal stem cells (MSCs) in an animal model, Salcedo et al [21,22] reported the functional recovery of anal resting pressure but could not detect cell differentiation or implanted MSCs at the injured site under confocal microscopy or in immuno uorescence assays.…”
Section: Discussionmentioning
confidence: 99%
“…It is somewhat different from ISR for human patients with rectal cancer. Finally, combination therapy with EMS and regenerative therapy may synergistically increase the effects of each treatment (7).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Several novel therapeutic options such as bulking agents, artificial bowel sphincter etc., have been proposed, but they are not completely accepted yet. Lately, several articles have reported that mesenchymal stem cells (MSC) can improve the function of the anal sphincter after an injury in animal models, including one from our own laboratory (6,7).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…In vitro and in vivo experimental studies using bioengineered human IAS have reported that implantation of intrinsically innervated human IAS constructs generated spontaneous basal tone with myogenic and neuronal components [ 13 , 14 ]. Furthermore, FI cell treatments [ 16 - 19 ] using bone mesenchymal stem cells (MSCs), adipose stem cells (ASCs), myoblasts, and a combined treatment strategy [ 20 - 24 ] have been reported functional improvement in the injured sphincter. However, these studies for cell therapy showed a bias and lacked data for clinical use as reported by the previous systematic reviews [ 25 - 27 ].…”
Section: Introductionmentioning
confidence: 99%